2003
DOI: 10.1007/s00276-003-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the carotico-clinoid foramen and its relation with the internal carotid artery

Abstract: The carotico-clinoid foramen is the result of ossification either of the carotico-clinoid ligament or of a dural fold extending between the anterior and middle clinoid processes of the sphenoid bone. It is anatomically important due to its relations with the cavernous sinus and its content, sphenoid sinus and pituitary gland. In this study the ossification state of the carotico-clinoid ligament, the diameter of the internal carotid artery and the carotico-clinoid foramen has been studied on 50 autopsy cases. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 15 publications
1
38
0
1
Order By: Relevance
“…The presence of an ossifi ed CCL is likely to cause compression and straightening of the internal carotid artery. 3 In the present case, the clinical history of the patient was not available to corroborate this observation.…”
Section: Discussionmentioning
confidence: 68%
“…The presence of an ossifi ed CCL is likely to cause compression and straightening of the internal carotid artery. 3 In the present case, the clinical history of the patient was not available to corroborate this observation.…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, certain ligaments which connect the different parts of the sphenoid bone occasionally ossify such as the pterygospinous (between the lateral pterygoid plate and the spine of sphenoid), the interclinoid (between the anterior and posterior clinoid processes) and the carotico clinoid (between the anterior and middle clinoid processes) [4].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 37 suggested that if interclinoid bars are present extending from anterior clinoid process, then combined extra and intradural approach should be adopted for removal of anterior clinoid process. The existence of Type I interclinoid bony bar or carotico-clinoid foramen may cause compression, tightening or stretching of the internal carotid artery 23 .…”
Section: Resultmentioning
confidence: 99%